2007
DOI: 10.1007/s00705-006-0918-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis B virus replication by shRNAs in stably HBV expressed HEPG2 2.2.15 cell lines

Abstract: In this study, the effect of RNAi on HBV replication was observed in a cell culture model, HepG2 2.2.15 cell line, which supports human HBV ayw replication and expression. Aim of the study was to investigate effects of shRNAs (small hairpin RNAs) targeting hepatitis B virus mRNAs on the viral replication in HepG2 2.2.15 cells. We selected three target HBV mRNA regions with different putative secondary structures to test whether the secondary structure of RNA may affect the inhibition efficacy on the target HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…13,14 A number of studies have verified that specific siRNAs targeting four open reading frames (ORFs) of HBV are efficient at inhibiting the expression of viral antigens and the replication of HBV DNA. [15][16][17][18] Fu et al designed and evaluated 23 siRNAs targeted throughout all four ORFs of HBV. The results showed that most of them were effective, but the siRNAs targeting different ORFs could lead to different efficacy in inhibiting HBV expression and replication.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A number of studies have verified that specific siRNAs targeting four open reading frames (ORFs) of HBV are efficient at inhibiting the expression of viral antigens and the replication of HBV DNA. [15][16][17][18] Fu et al designed and evaluated 23 siRNAs targeted throughout all four ORFs of HBV. The results showed that most of them were effective, but the siRNAs targeting different ORFs could lead to different efficacy in inhibiting HBV expression and replication.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, two approaches have been developed to deliver extra siRNA into cells for the preselection of effective siRNAs, namely transient delivery of chemically synthesized siRNA and expression of siRNA intracellularly from vectors [27]. Vector-based RNAi has particular advantages, considering the likelihood of RNAse contamination, relatively short half-life and the great costs associated with chemically synthesized siRNA [28]. In addition, transgenic vector-based RNAi could function as an alternative method of gene silencing in vivo [29].…”
Section: Discussionmentioning
confidence: 99%
“…Specific gene silencing also can be triggered in mammalian cells by using synthetic short interfering RNA (siRNA), and plasmid or virus-mediated short hairpin RNA (shRNA). These RNAi strategies have been used successfully for suppressing the replication of human and animal viruses, including hepatitis B virus (HBV) (Kayhan et al, 2007), human immunodeficiency virus type (HIV) (Coburn and Cullen, 2002), porcine reproductive and respiratory syndrome virus (PRRSV) (Luo et al, 2013) and foot-and-mouth disease virus (FMDV) (De los Santos et al, 2005;Lv et al, 2009;Xu et al, 2012). Furthermore, we and others reported that transgenic animals expressing shRNA against virus genes showed a significant resistance to viral challenge (Pengyan et al, 2010;Li et al, 2014;Daniel-Carlier et al, 2013;Du et al, 2014).…”
Section: Introductionmentioning
confidence: 94%